Comparison of three types of laser optical disdrometers under natural rainfall conditions. Issue 4 (11th March 2020) - Johannsen, Lisbeth Lolk; Zambon, Nives; Strauss, Peter; Dostal, Tomas; Neumann, Martin; Zumr, David; Cochrane, Thomas A.; Blöschl, Günter; Klik, Andreas
ABSTRACT: Optical disdrometers can be used to estimate rainfall erosivity; however, the relative accuracy of different disdrometers is unclear. This study compared three types of optical laser-based disdrometers to quantify differences in measured rainfall characteristics and to develop correction factors for kinetic energy (KE). Two identical PWS100 (Campbell Scientific), one Laser Precipitation Monitor (Thies Clima) and a first-generation Parsivel (OTT) were collocated with a weighing rain gauge (OTT Pluvio 2 ) at a site in Austria. All disdrometers underestimated total rainfall compared to the rain gauge with relative biases from 2% to 29%. Differences in drop size distribution and velocity resulted in different KE estimates. By applying a linear regression to the KE–intensity relationship of each disdrometer, a correction factor for KE between the disdrometers was developed. This factor ranged from 1.15 to 1.36 and allowed comparison of KE between different disdrometer types despite differences in measured drop size and velocity.